Association Between Neurohormone Levels and Exercise Testing Measures in Patients with Mechanical Circulatory Supports. Issue 8 (August 2020) - Grosman-Rimon, Liza; Kachel, Erez; McDonald, Michael A.; Lalonde, Spencer D.; Yip, Paul; Ribeiro, Roberto V.P.; Adamson, Mitchell B.; Cherney, David Z.; Rao, Vivek
Abstract : Continuous-flow left ventricular assist device (CF-LVAD) recipients exhibit impaired exercise capacity. Long-term continuous blood flow also elevates norepinephrine (NE) and aldosterone (Aldo) levels. However, the relationship between exercise capacity and neurohormonal activation has not been elucidated. Our study objective was to assess the association between cardiopulmonary exercise testing (CPT) measures and neurohormonal levels in CF-LVAD recipients. Symptom-limited CPT on a treadmill, using the modified Bruce protocol was performed in 15 CF-LVAD recipients. Norepinephrine and Aldo levels were measured, and the association between their levels and CPT measures were assessed. Peak VO2 (13.6 ml/kg/min) and percent age, sex predicted VO2 max (49.4%), and oxygen pulse (O2 pulse) (9.0 ± 4.0 ml/beat) were low, whereas minute ventilation/carbon dioxide output (VE/VCO2 ) slope (35) was elevated. In addition, VO2 at anaerobic threshold (VO2 AT), and O2 pulse values negatively correlated with NE levels. Norepinephrine levels positively correlated with chronotropic responses and heart rate (HR) recovery. Aldo levels in CF-LVAD recipients were not related to any CPT measures. Continuous-flow left ventricular assist device recipients exhibited impaired exercise capacity and chronotropic incompetence (CI). Despite the association of NE levels with chronotropic responses at peak exercise, neither NE levels nor chronotropic responses predicted peak VO2. This suggests that CI may not be the primary factor responsible for the low peak VO2. O2 pulse, which is a combined measure for stroke volume and peripheral oxygen extraction during exercise, was an independent predictor of peak VO2 . Future studies should examine the contribution of peripheral factors to exercise capacity limitations.